Breast lumps: rare presentation of oat cell carcinoma of lung. Issue 2 (February 1988) - Kelly, C; Henderson, D; Corris, P
Abstract : Two cases of oat cell carcinoma are described. Both patients presented initially with a lump in the breast. A review of the published reports on breast metastases as a presenting feature of malignant disease was performed and lung cancer was found to be the commonest extramammary tumour to present as a breast mass (80% of cases) and usually as small cell carcinoma.